2002
DOI: 10.1523/jneurosci.22-15-06372.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Neuronal Glutamate Transporter Contributes to Neurotransmitter GABA Synthesis and Epilepsy

Abstract: The predominant neuronal glutamate transporter, EAAC1 (for excitatory amino acid carrier-1), is localized to the dendrites and somata of many neurons. Rare presynaptic localization is restricted to GABA terminals. Because glutamate is a precursor for GABA synthesis, we hypothesized that EAAC1 may play a role in regulating GABA synthesis and, thus, could cause epilepsy in rats when inactivated. Reduced expression of EAAC1 by antisense treatment led to behavioral abnormalities, including staring-freezing episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(194 citation statements)
references
References 52 publications
12
178
1
3
Order By: Relevance
“…EAAT3, in hippocampal slices decreased the inhibitory neurotransmitter ␥-aminobutyric acid (GABA)-mediated inhibitory postsynaptic current and miniature inhibitory postsynaptic current due to a reduction of GABA synthesis because glutamate uptaken by neuronal EAATs is a substrate for GABA synthesis (22). These results are consistent with the data from an early study showing that antisense knockdown of EAAT3 induced epilepsy in rats and that the hippocampal slices from these rats had a decrease in GABA synthesis, total GABA levels, and miniature inhibitory postsynaptic current (23). Thus, EAAT3 plays a role in maintaining the balance of glutamate/GABA neurotransmission.…”
Section: Discussionsupporting
confidence: 85%
“…EAAT3, in hippocampal slices decreased the inhibitory neurotransmitter ␥-aminobutyric acid (GABA)-mediated inhibitory postsynaptic current and miniature inhibitory postsynaptic current due to a reduction of GABA synthesis because glutamate uptaken by neuronal EAATs is a substrate for GABA synthesis (22). These results are consistent with the data from an early study showing that antisense knockdown of EAAT3 induced epilepsy in rats and that the hippocampal slices from these rats had a decrease in GABA synthesis, total GABA levels, and miniature inhibitory postsynaptic current (23). Thus, EAAT3 plays a role in maintaining the balance of glutamate/GABA neurotransmission.…”
Section: Discussionsupporting
confidence: 85%
“…This effect was likely to be produced via a presynaptic mechanism, because it was associated with an increase in the paired-pulse ratio evoked IPSCs and a reduction in the frequency but not the amplitude of spontaneous miniature IPSCs, as demonstrated previously for opioids and cannabinoids in the PAG (Vaughan and Christie, 1997;Vaughan et al, 2000). The lack of effect on miniature IPSC amplitude and kinetics also indicates that, under our experimental conditions, TBOA did not reduce GABAergic transmission via disruption of presynaptic glutamate transporter-mediated GABA synthesis, as has been demonstrated at other CNS synapses (Sepkuty et al, 2002;Mathews and Diamond, 2003).…”
Section: Presynaptic Inhibition Of Gabaergic Transmission By Glutamatsupporting
confidence: 75%
“…Depleting or enhancing intraterminal cytoplasmic concentrations of neurotransmitter would therefore be expected to decrease or enhance vesicle content, respectively, as has been observed experimentally in various synapses (Murphy et al, 1998;Pothos et al, 1998), including hippocampal inhibitory synapses (Engel et al, 2001;Sepkuty et al, 2002;Mathews and Diamond, 2003). A recent study consistent with this idea demonstrated that GABA vesicle content is in dynamic equilibrium with intraterminal glutamate concentrations (Mathews and Diamond, 2003).…”
Section: Introductionmentioning
confidence: 69%